Conducting your pharmacy practice research project : a step-by-step approach - Smith, Felicity, 1958- (London ; Chicago : Pharmaceutical Press, 2010)
This clear and concise handbook considers the stages of the research process in logical order, from planning of the project through to dissemination of the findings
Part 1: Preparation, planning and management - 1. Introduction; 2. Setting up the project, protocol development and ethics; 3. Time management and working with others; 4. For Supervisors. Part 2: Scientific enquiry and research methodology - 5. A scientific approach to your research; 6. Reviewing the literature; 7. Types of study and research design; 8. Sources of information, datasets, sampling and recruitment; 9. Data collection: survey research and questionnaires; 10. Data collection: interviews and focus groups; 11. Data collection: prospective methods; 12. Existing datasets and secondary analysis; 13. Data processing and analysis. Part 3 Writing up and dissemination of the findings - 14. The project report; 15. Dissemination of the findings
Includes index.
Keywords: Pharmaceutical Services; Health Services Research -- methods; Professional Practice; Research Design; Pharmacy -- Research; Pharmacy -- Practice